Edukasi Undang-Undang Nomor 8 Tahun 2016 Tentang Penyandang Disabilitas di Kecamatan Sewon Kabupaten Bantul - Suparman Marzuki; despan heryansyah (UII, 2019)
The poor public servants of persons with disabilities are caused by many things, ranging from the educational background of village government officials, to the culture that has lived and developed in the community that people with disabilities cannot be equated with other normal people. However, efforts to create public services that are equal and friendly to persons with disabilities must continue, this is not only in order to protect the human rights of every citizen but also in carrying out the mandate of the constitution. Facing this condition, the Indonesian Government then issued Law Number 8 of 2016 concerning Persons with Disabilities. This law is the basis and reference for the government in providing services to persons with disabilities with a basic concept of respect for human dignity. The basis of service for persons with disabilities is at least related to two things, the main focus of which is on removing barriers. First, the availability of facilities and facilities available to reach persons with disabilities. Second, the paradigm of the government or government apparatus for persons with disabilities in providing public services. Sewon Subdistrict was used as an object of service because it considered quite a lot of disability operators. Indeed, until now, there is no definite number of persons with disabilities in Sewon sub-district, because the government itself does not conduct the database. Admittedly, this is one of the weaknesses that have occurred so far, let alone responsiveness and response to a number of problems they face, even the data collection on the number of the local government does not have it